2009
DOI: 10.1128/mcb.01481-08
|View full text |Cite
|
Sign up to set email alerts
|

Bim Upregulation by Histone Deacetylase Inhibitors Mediates Interactions with the Bcl-2 Antagonist ABT-737: Evidence for Distinct Roles for Bcl-2, Bcl-xL, and Mcl-1

Abstract: The Bcl-2 antagonist ABT-737 kills transformed cells in association with displacement of Bim from Bcl-2. The histone deactetylase (HDAC) inhibitor suberoyl bis-hydroxamic acid (SBHA) was employed to determine whether and by what mechanism ABT-737 might interact with agents that upregulate Bim. Expression profiling of BH3-only proteins indicated that SBHA increased Bim, Puma, and Noxa expression, while SBHA concentrations that upregulated Bim significantly potentiated ABT-737 lethality. Concordance between SBHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 74 publications
(124 reference statements)
7
115
2
Order By: Relevance
“…The lower acetylation levels reported from ZGA till blastocyst, when HDAC1 reaches peak expression implies a requirement for HDAC1 to tide over ZGA. The requirement of BCLXL for ZGA was also evident from the expression pattern observed [51]. The lower levels of HDAC1 under in vitro condition may indicate a comparatively poor reprogramming of genome.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The lower acetylation levels reported from ZGA till blastocyst, when HDAC1 reaches peak expression implies a requirement for HDAC1 to tide over ZGA. The requirement of BCLXL for ZGA was also evident from the expression pattern observed [51]. The lower levels of HDAC1 under in vitro condition may indicate a comparatively poor reprogramming of genome.…”
Section: Resultsmentioning
confidence: 67%
“…It was demonstrated that, when the expression of HDAC1 is inhibited, expression of BCLXL goes down and results in apoptosis [51]. Studies conducted on mouse preimplantation embryos have also demonstrated the crucial role of BCLXL in protecting the embryos to enter ZGA phase [28,29].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…147,148 Potently, its binding activity disrupts the interactions of these pro-survival proteins with their pro-apoptotic counterparts, leading to activation of BH3-only proteins including BIM and BID, which in turn sensitize cells to or trigger apoptosis. This mechanism involves an increase in cleaved fragments of PARP, and caspase-8 and cytochrome C levels shortly after treatment with ABT-737 at low micromolar concentrations.…”
Section: Mcl1mentioning
confidence: 99%
“…It seems that the extent of Bcl-2 bound to Bim, rather than total Bcl-2 expression levels, may determine cellular sensitivity to ABT-737 (Deng et al 2007). In hand with this, ABT-737 has been shown to interact with certain anticancer agents capable of up-regulating BIM, (Kuroda et al 2006;Zhang et al 2008) including histone deacetylase inhibitors (HDACi) (Chen et al 2009). However, ABT-737 could synergize with HDACi in vitro to kill lymphoma cells over-expressing Bcl-2 and Bcl-X L (Whitecross et al 2009).…”
Section: Introductionmentioning
confidence: 99%